Perancangan Sistem Perangkap Hama Tanaman Petani Otomatis Menggunakan Modul Mikrokontroler Arduino - Rahmat Tampune Bangun; Hasanul Fahmi (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
An animal can also be called a pest if it causes damage to natural ecosystems or acts as an agent for spreading disease in human habitats. The pest in question is a mouse-like animal that aims to make a trap using a load cell weight sensor with an Arduino microcontroller module. The scope of the problem in this research is the cultivation of maize and paddy fields in Mardingding District, Karo Regency. For testing purposes, 3 trials are used, respectively, corn and rice fields. The variable is limited to animals the size of a mouse. The purpose of this research is to build a plant pest trapping device using the Arduino uno micro controller module which can make it easier to catch pests efficiently. Farmers no longer need to control within a certain period of time. so it can save time and energy to do other jobs. The application is built using the programming language used is the C language and the Arduino IDE with notification to farmers only via short messages via cellphones.